2016
DOI: 10.1038/pr.2016.245
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in hypoxic ischemic encephalopathy during therapeutic hypothermia

Abstract: The HF component of HRV is increased in infants with moderate HIE undergoing TH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 27 publications
3
41
1
Order By: Relevance
“…Eight studies were excluded, 2 of which [21, 22] measured the severity of brain injury with methods that did not meet the criteria for this review (Table 4). These studies reported significant differences in mean HRV between severity groups, as well as between survivors and non-survivors.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were excluded, 2 of which [21, 22] measured the severity of brain injury with methods that did not meet the criteria for this review (Table 4). These studies reported significant differences in mean HRV between severity groups, as well as between survivors and non-survivors.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 43 fulltext studies were assessed for eligibility. Of these, four studies met the inclusion criteria and were submitted to data extraction and analysis [19][20][21][22]. Furthermore, 139 studies from the reference lists of the included studies were screened but none of these were included (Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Goulding et al 2017 [22] included all term neonates with HIE from 2009 to 2014 admitted to a single NICU for therapeutic hypothermia. The HIE eligibility criteria were identical with Goulding et al 2015 [21].…”
Section: Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the true predictive ability of fetal ECG can only be determined once it is collected at a sampling rate that preserves more of the underlying physiological information. We have demonstrated this approach to assess the severity of hypoxic ischaemic encephalopathy (HIE) in the immediate newborn period (Goulding et al, 2017). Animal and human studies show that the current mode of ECG acquisition is outdated, imprecise, and discards important predictive information (Durosier et al, 2014; Li et al, 2015).…”
mentioning
confidence: 99%